Current Summary Of Surface Integrity When Machining Inconel 718 Under Different Cooling And Lubrication Strategies - Kasim, Mohd Shahir; Husshini, Nur Husnina Najeah; Raja Abdullah, Raja Izamshah; Mohd Shahrim, Mohammad Shah All Hafiz; W. Mohamad, W Noor Fatihah; Md Ali, Mohd Amran; Abu Bakar, Mohd Hadzley (Malaysian Tribology Society (Mytribos), 2021)
Cutting tool creates friction, and the materials go through the deformation phase that leads to the generation of heat during machining process. Inconel is a superior material that is broadly used in the aerospace industry to make turbine casings, discs, and engine shafts. The greater challenge which will be faced when the process takes place is due to the relatively low conductivity of heat with 11.4 W/m.K. Therefore, the heat generated will focus in the vicinity of the cutting area which creates trouble for heat dissipation and may lead to destruction of surface integrity. To avoid work hardening of the machined surface, a few strategies of cooling and lubrication had been proposed. This paper aims to review the best method of cooling and lubricating on difficult-to-cut materials. This study is crucially essential to improve the machining performance regarding surface integrity as the surface condition of materials is a major concern in aerospace application.